Exploring Challenges and Prospects of Solar Energy Entrepreneurship of Accra Metropolis in Ghana - Oscar Agyemang Opoku; Lord Ebo Sampson; Henry Okudzeto; Jesse Azebiik Anak (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The demand for power in Ghana is increasing at a pace of 10% each year. To shift away from traditional energy-intensive economic development and its negative environmental impact, the government has begun to heavily promote the development of solar photovoltaic technology. This study explored the challenges and potential of solar energy entrepreneurship as well as the capacity of solar energy enterprises in the production and supply of solar energy, and the methodologies for implementing solar energy businesses in Ghana's Accra Metropolis. The research took a qualitative approach and used an exploratory design. The data were analysed thematically with the aid of NVivo version 11.0. In comparison to predicted market demands, solar energy firms did not have the resources to produce and supply solar energy. In addition, to promote their operations in Ghana, solar energy companies have used techniques such as discounts, installment payments, and price reductions for goods and services. Furthermore, high-interest rates, inadequate incentives, insufficient access to finance, and a lack of technical know-how for the operation and maintenance of solar energy technology were all obstacles to investment in solar energy generation. Notwithstanding the difficulties associated with its operations, the prospects for solar energy production in Ghana remain bright. The study recommended that the Ministry of Energy, in collaboration with renewable energy technology companies, educate the public about the benefits of solar energy technologies; the Ministry of Energy, in partnership with the government, ensure that the promise made in the energy policy of a 50% tax reduction on all imports of electrical goods is achieved. Moreover, financial institutions should make it easier for energy-producing firms to obtain credit.